Can Science and Technology Save China? - Greenhalgh, Susan 1949-; Zhang, Li 1965- (Cornell University Press, 2020)
Can Science and Technology Save China? assesses the intimate connections between science and society in China, offering an in-depth look at how an array of sciences and technologies are being made, how they are interfacing with society, and with what effects.Focusing on critical domains of daily life, the chapters explore how scientists, technicians, surgeons, therapists, and other experts create practical knowledges and innovations, as well as how ordinary people take them up as they pursue the good life. Editors Greenhalgh and Zhang offer a rare, up-close view of the politics of Chinese science-making, showing how everyday logics, practices, and ethics of science, medicine, and technology are profoundly reshaping contemporary China. By foregrounding the notion of "governing through science," and the contested role of science and technology as instruments of change, this timely book addresses important questions regarding what counts as science in China, what science and technology can do to transform China, as well as their limits and unintended consequences